Toward a theoretical framework for task design in mathematics education - Radmehr, Farzad (Journal on Mathematics Education, 2023)
Task design is an important element of effective mathematics teaching and learning. Past research in mathematics education has investigated task design in mathematics education from different perspectives (e.g., cognitive and cultural) and offered a number of (theoretical) frameworks and sets of principles. In this study, through a narrative research in the form of autoethnography, I reflected on my past teaching and research experience and proposed a (theoretical) framework for task design in mathematics education. It contains four main principles: (a) inclusion, (b) cognitive demand, (c) affective and social aspects of learning mathematics, and (d) theoretical perspective(s) toward learning mathematics. This framework could be used as a tool for critically reflecting on current practices in terms of task design in teaching mathematics and research in mathematics education. It may also contribute to ongoing research in mathematics education about task design and enable or enhance opportunities for dialogue between lecturers, teachers, and researchers about how to design rich mathematical tasks for teaching and research purposes.